Implementation of Isak 35 To Roudlotul Jannah Mosque Entities Perum Bumirejo Sukodono Lumajang - Sochib, Sochib (IMPOWERMENT SOCIETY, 2023)
Abstract The purpose of this community service is to obtain an overview of the implementation of accounting in mosque entities at the Roudlotul Jannah Mosque. Does the financial report of the mosque entity apply the ISAK 35 accounting standard as a non-profit oriented entity? The method used in this service is by analyzing accounting practices in mosque entities that have been carried out by mosque administrators or takmir. Furthermore, mosque administrators were given a transfer of information related to ISAK 35. Observations were made of transactions and records carried out by mosque entity administrators during the 2021 period. Data collection techniques used interview and documentation techniques. Based on the results of the dedication carried out, it can be concluded that the accounting applied in the Roudlotul Jannah Mosque entity still uses single entry bookkeeping. The management or takmir of the Roudlotul Jannah Mosque still does not use the accounting standards that apply to non-profit-oriented entities, namely ISAK 35. The next impact is that the management of the Roudlotul Jannah mosque cannot prepare annual financial reports according to ISAK 35.